Pengaruh Inovasi, Penggunaan Teknologi Informasi dan Penggunaan Informasi Akuntansi Terhadap Kinerja UMKM Di Kabupaten Rembang - Muhammad Kelvin Zudhianshah; Nurma Gupita Dewi (Jurnal Ekonomika dan Bisnis, 2023)
This study aims to demonstrate and examine the effect of innovation, information technology, and accounting information on the performance of MSMEs in Rembang Regency. The technique used, namely purposive sampling, was used to sample 50 MSME actors in Rembang Regency. The data source uses subject data in this data using primary data obtained using a questionnaire. SPSS application version 19 is used to test the validity, reliability and hypotheses. This test was carried out on 50 MSME actors in Rembang Regency whose businesses used information technology and used accounting information. Based on research findings on innovation, the use of information technology and the use of accounting information have a significant positive effect on the performance of SMEs.